Living Hadith in Honey-Based Therapy: Analysis of its Application in Diabetes Treatment at Miftahussyifa Alternative Medicine, Medan - M Hafiz Rustandi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2025)
One alternative treatment for diabetes is honey therapy. Honey contains sufficient water content and moisture levels that do not support bacterial growth and development. The purpose of this study is to examine the application of honey therapy for diabetes treatment within the living hadith framework. This research employs an observational process that includes monitoring locations and activities occurring in social contexts. Interviews were conducted using a structured guide to record relevant data. The collected data was then analyzed through an interactive method, which includes data reduction, data presentation, as well as drawing conclusions and verification. The research results indicate that honey therapy within this living hadith context can serve as an alternative treatment for healing diabetic wounds